1715 N.C. Sess. Laws 29 - (:unkn) unknown (My University, 1715)
The Militia of this Government shall consist of all the Freemen within the same between the years of Sixteen years & Sixty. This included free blacks. Each militiaman had to provide himself with "a good Gun well-fixed Sword & at least Six Charges of Powder & Ball."
Keywords: MILITIAS; REQUIRED POSSESSION